Deconstructing high performance Nordic sport: the case study of women's handball (the 'team as method'). Issue 4 (3rd April 2019) - Hemmestad, Liv B.; Jones, Robyn L.
Abstract: The principal purpose of this study was to record and explore the changing coaching landscape within elite Norwegian women's handball from 2003 to 2005. This was in relation to critically understanding the culture created within the context, and the precise role(s) of head coach Marit Breivik, the assistant coaches, and the athletes in question, in its creation. The significance of the paper lies in enhancing understanding the 'Nordic model' of society, inclusive of its emphasis on equality, tolerance, consensus and cooperation, and the ways in which this is constructed, explored and challenged within and through sport. When appointed in 1994, Breivik inherited a high performance system not unlike any other in international sport; one dominated by metrics, compliance and control. It was one she wanted to change to better reflect the Nordic values of integration, interdependence and egalitarianism. The study's method comprised an in depth ethnography where the principal author spent two years embedded within the setting. The results, deduced from inductive analysis of the collected data, are discussed in terms of two principal themes. First, the initial attempts at culture change by Breivik and the inevitable resistance experienced; and second, the relational strategy she adopted to overcome such resistance (including that of establishing the 'team as method'). Finally, a conclusion reflects on the meaning of such findings, touching on the dual explanatory notions of 'progressive repair' and that of the coach as a 'virtuoso actor'.